Phase II Study with 5-Fluorouracil and Ginkgo biloba Extract (GBE 761 ONC) in Patients with Pancreatic Cancer - Hauns, Bernhard; Häring, Brigitte; Köhler, Stephan; Mross, Klaus; Robben-Bathe, Petra; Unger, Clemens (Arzneimittelforschung, 1999)
The aim of the study was to evaluate the efficacy and tolerability of as well as the quality of life under treatment with 5-fluorouracil (CAS 51-21-8, 5-FU) combined with parenteral GBE 761 ONC (i.e. the ginkgo biloba special extract EGb 761) in patients with pancreatic cancer. Forty-eight patients with locally or metastatic advanced pancreatic cancer were treated within a phase II study. The treatment was repeated every three weeks until progression. Response to therapy was evaluated after 2 and 4 treatment courses.Thirty-two patients were evaluable for response. Progressive disease was observed in 22 (68.8%) patients, no change in 7 (21.9%) patients and partial response in 3 (9.4%) patients (overall response = 9.4%).GBE 761 ONC was well tolerated. Adverse events which occurred during the study consisted mainly of myelosuppression and gastrointestinal symptoms and were judged as 5-FU-related or consisted of liver toxicity, respectively, and were judged as tumour-related.These results suggest a good benefit-risk ratio of the combination of 5-FU and GBE 761 ONC in the treatment of pancreatic cancer. In comparison with the results of studies with either 5-FU or gemcitabine as single agents the combination of 5-FU / GBE 761 ONC shows comparable response rates. The toxicity of the 5-FU / GBE 761 ONC combination was low. This combination therapy therefore warrants further clinical investigation, such as a controlled clinical trial against 5-FU or gemcitabine monotherapy.
Keywords: CAS 51-21-8; EGb 761, first line therapy, phase II study; 5-Fluorouracil; Ginkgo biloba extract; Pancreatic cancer